Associations between cardiometabolic index with kidney stones: evidence from NHANES 2007-2018 - Zhong, Suquan; Li, Guoliang; Tian, Chao; Jiang, Maolin; Chen, Dong; Wang, Hangtao; Diao, Pengfei (Frontiers in Endocrinology, 2025)
BackgroundKidney stones are a prevalent disorder that is linked to a range of metabolic variables. The cardiometabolic index (CMI) is a newly developed combined measure used to evaluate the state of cardiometabolic health. Nevertheless, the association between CMI and kidney stone remains little investigated.MethodsIn this study, cross-sectional analysis was done on NHANES data from 2007 to 2018. The association between the prevalence of kidney stones and the CMI was investigated using a logistic regression analysis. To look into the nonlinear link between them, we used restricted cubic spline (RCS) analysis. The study was made more reliable and accurate by using sensitivity analysis and subgroup analysis to look for factors that may have contributed to the different results.ResultsA significant association was seen between increased CMI and the prevalence of kidney stones (OR = 1.19, 95% CI: 1.06-1.32). The RCS analysis revealed crucial CMI values that exhibited a robust association within a certain range. Subgroup studies revealed that this link was particularly prominent among those below the age of 50, females, obese, CKD and diabetes patients. The dependability of the study’s conclusions was further established using sensitivity analysis.ConclusionThis study established a notable association between CMI and a higher prevalence of kidney stones, emphasizing the significance of CMI as a comprehensive measure for evaluating metabolic risk. Furthermore, it suggests that monitoring CMI levels could be beneficial in identifying populations with a high prevalence of kidney stones.